No protection, no justice: Women murders in Tamaulipas - García-Santiago, Abad (Universidad Autónoma de Tamaulipas, 2010)
This article shows the social and demographic characteristics of female victims during the year 2009 in Tamaulias. The data is the result of the information taken from the Centro de Estudios Fronterizos y Promotor de los Derechos Humanos in Reynosa, Tamaulipas. During this period the study presented 46 cases of murdered wome; the group that represents the most vulnerability is the one made up of women between 31-40 years of age. Married women find themselves being the ones that show more cases of this social  phenomenon and in a big part the victims were no strangers to the aggressor. The death of these women where mainly produced by punches and the bodies of a big part of them were left forgotten usually in dumpsters or dirtroads. Most of these cases were reported near the border with the U.S. in places like Reynosa, Nuevo Laredo, Matamoros and Rio Bravo.